2014
DOI: 10.1523/jneurosci.2166-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Correlates of Stimulus-Specific Adaptation

Abstract: Stimulus-specific adaptation (SSA) is the reduction in response to a common stimulus that does not generalize, or only partially generalizes, to rare stimuli. SSA is strong and widespread in primary auditory cortex (A1) of rats, but is weak or absent in the main input station to A1, the ventral division of the medial geniculate body. To study SSA in A1, we recorded neural activity in A1 intracellularly using sharp electrodes. We studied the responses to tone pips of the same frequency in different contexts: as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
88
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(107 citation statements)
references
References 42 publications
19
88
0
Order By: Relevance
“…As pointed out previously (Farley et al, 2010), the higher response to the deviant might have been due to a greater cross-stimulus adaptation in the equiprobable compared with the oddball sequence. The importance of cross-stimulus adaptation in the equiprobable control conditions has been demonstrated by Taaseh et al (2011) and Hershenhoren et al (2014) in single-unit recordings in the auditory cortex of anesthetized rats. This group also found that the responses to the deviant in the oddball sequences were underestimated by a model that incorporates cross-frequency adaptation, suggesting a real surprise response.…”
Section: Discussionmentioning
confidence: 83%
“…As pointed out previously (Farley et al, 2010), the higher response to the deviant might have been due to a greater cross-stimulus adaptation in the equiprobable compared with the oddball sequence. The importance of cross-stimulus adaptation in the equiprobable control conditions has been demonstrated by Taaseh et al (2011) and Hershenhoren et al (2014) in single-unit recordings in the auditory cortex of anesthetized rats. This group also found that the responses to the deviant in the oddball sequences were underestimated by a model that incorporates cross-frequency adaptation, suggesting a real surprise response.…”
Section: Discussionmentioning
confidence: 83%
“…Although the adaptation in narrow frequency channels model presents a simple feedforward mechanism for the generation of SSA from the upstream driving inputs, it has been shown that the model is insufficient to fully account for the properties of SSA seen in primary auditory cortex (A1) (Hershenhoren et al, 2014; Yaron et al, 2012), suggesting that there are also locally generated mechanisms of SSA. In A1, there are a variety of cell types classified broadly into excitatory and inhibitory neurons that form complex cortical circuits which are proposed to enhance SSA (Taaseh et al, 2011).…”
Section: Differential Adaptation Of Specific Populations Of Tuned Neumentioning
confidence: 99%
“…Indeed, computational models based on purely feed-forward connectivity show SSA [4,25,26]. However, these models provide predictions that are inconsistent with some of the experimental data [4,12]. Here we study an alternative mechanism: SSA may arise from the heavily recurrent cortical connectivity and the depression of the local, intracortical synapses in A1 [27].…”
Section: Introductionmentioning
confidence: 98%
“…Although SSA is present in the inferior colliculus [57] and the auditory thalamus [811], it is mostly confined to the non-lemniscal pathway [8,9] and is thus likely generated de novo in A1, whose major thalamic input is from the lemniscal part of the medial geniculate body. SSA in A1 has true deviance sensitivity: The response to a rare stimulus presented within a sequence composed mostly of the same standard tone (which violates the expectation for yet another repeat of the standard) is larger than the response to the same rare stimulus when presented within a sequence composed of many different tones (that doesn't generate strong expectations for any stimulus) although the level of sensory adaptation in the multi-tone sequence may be lower [4,12,13]. SSA is therefore an appealing test case for linking high-level concepts such as deviance sensitivity with mechanistic models.…”
Section: Introductionmentioning
confidence: 99%